2018
DOI: 10.1177/0022034518792567
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Dental Implant Use in the U.S., 1999–2016, and Projections to 2026

Abstract: Dental implants have become an increasingly popular treatment choice for replacing missing teeth. Yet, little is known about the prevalence and sociodemographic distribution of dental implant use in the United States. To address this knowledge gap, we analyzed data from 7 National Health and Nutrition Examination Surveys from 1999 to 2016. We estimated dental implant prevalence among adults missing any teeth for each survey period overall as stratified by sociodemographic characteristics. We calculated absolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
281
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 373 publications
(299 citation statements)
references
References 24 publications
4
281
1
13
Order By: Relevance
“…Additionally, our study's prevalence is similar to the prevalence reported in previous studies in other countries. For example, in a recent study from the USA, the prevalence of dental implant use rose from 0.7% in 1999 to 2000 to 5.7% in 2015 to 2016. In Switzerland, the prevalence of dental implant use in 2002 was 4.4%.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Additionally, our study's prevalence is similar to the prevalence reported in previous studies in other countries. For example, in a recent study from the USA, the prevalence of dental implant use rose from 0.7% in 1999 to 2000 to 5.7% in 2015 to 2016. In Switzerland, the prevalence of dental implant use in 2002 was 4.4%.…”
Section: Discussionmentioning
confidence: 98%
“…Our results are consistent with the results of three previous studies from the USA. Those studies reported an increase in the odds ratio for dental implant use among the higher SES groups. However, none of these studies examined the association of income level as a predictor of dental implant use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations